Principal Management in Realizing Adiwiyata Schools: A Qualitative Study of Environmental Education Leadership in Indonesian Secondary Schools - Lina Mulyani; Lilis Suwandari (ITScience (Information Technology and Science), 2026)
This study explores how principals' management practices contribute to the successful implementation of the Adiwiyata School program, an effort to promote environmental education and sustainable school culture. Employing a qualitative descriptive case study design, the research was conducted at SMP Negeri 1 Ciamis and MTs Negeri 5 Ciamis, Indonesia. Data were collected through in-depth interviews, field observations, and document analysis, and analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings reveal that principals’ managerial and leadership capacities strongly influence the effectiveness of the Adiwiyata program. Strategic planning, collaborative organization, consistent implementation of environmental activities, and continuous evaluation enabled the embedding of environmental values in daily school practices and learning processes. The study also identifies persistent challenges, including limited resources, time constraints, and varying levels of environmental awareness among school members. These challenges were addressed through adaptive leadership, participatory decision-making, and collaboration with external stakeholders. The study concludes that environmental education initiatives cannot be sustained through procedural compliance alone, but require strong school leadership and institutional readiness. This research contributes to educational management literature by highlighting principal management as a key mediating factor linking environmental education policy to sustainable school practices.